Relative Fitness of Helicoverpa armigera (Lepidoptera: Noctuidae) on Seven Host Plants: A Perspective for IPM in Brazil. Issue 1 (21st January 2016) - Reigada, C.; Guimarães, K. F.; Parra, J. R. P.
Abstract: The cotton bollworm Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) is a widespread pest of many cultivated and wild plants in Europe, Africa, Asia, and Australia. In 2013, this species was reported in Brazil, attacking various host crops in the midwestern and northeastern regions of the country and is now found countrywide. Aiming to understand the effects of different host plants on the life cycle of H. armigera, we selected seven species of host plants that mature in different seasons and are commonly grown in these regions: cotton ( Gossypium hirsutum, "FM993"), corn ( Zea mays, "2B587"), soybean ( Glycine max, "99R01"), rattlepods ( Crotalaria spectabilis ), millet ( Pennisetum glaucum, "ADR300"), sorghum ( Sorghum bicolor, "AGROMEN70G35"), and cowpea ( Vigna unguiculata, "SEMPRE VERDE"). The development time of immatures, body weight, survivorship, and fecundity of H. armigera were evaluated on each host plant under laboratory conditions. The bollworms did not survive on corn, millet, or sorghum and showed very low survival rates on rattlepods. Survival rates were highest on soybean, followed by cotton and cowpea. The values for relative fitness found on soybean, cotton, cowpea, and rattlepods were 1, 0.5, 0.43, and 0.03, respectively. Survivorship, faster development time, and fecundity on soybean, cotton, and cowpea were positively correlated. Larger pupae and greater fecundity were found on soybean and cotton. The results indicated that soybean, cotton, and cowpea are the most suitable plants to support the reproduction of H. armigera in the field.